Feasibility of human lung ventilation imaging using highly polarized naturally abundant xenon and optimized three‐dimensional steady‐state free precession. Issue 2 (27th April 2015) - Stewart, Neil J.; Norquay, Graham; Griffiths, Paul D.; Wild, Jim M.
<x xml:space="preserve">Abstract</x> Purpose To demonstrate the potential for high quality MRI of pulmonary ventilation using naturally abundant xenon (NAXe) gas. Methods MRI was performed at 1.5 Tesla (T) and 3 T on one healthy smoker and two healthy never‐smokers. 129Xe gas was polarized to ∼25% using an in‐house spin‐exchange optical pumping polarizer fitted with a laser diode array with integrated volume holographic grating and optical train system. Volunteers inhaled 1 L of NAXe for an 8 to 15 s breathhold while MR images were acquired with full‐lung coverage using a three‐dimensional steady‐state free precession sequence, optimized for maximum signal‐to‐noise ratio (SNR) at a given spatial resolution. For the purpose of image quality comparison, the MR acquisition was repeated at 1.5 T with 400 mL enriched xenon and 200 mL 3He. Results All NAXe lung images were of high quality, with mean SNRs of 25–40 (voxel 4.2 × 4.2 × 8/10 mm3) and ∼30% improvement at 3 T versus 1.5 T. The high SNR permitted identification of minor ventilation defects in the healthy smoker's lungs. NAXe images were of comparable SNR to those obtained with enriched xenon and 3He. Conclusion Optimization of MR pulse sequences and advances in polarization technology have facilitated high quality pulmonary ventilation imaging with inexpensive NAXe gas. Magn Reson Med 74:346–352, 2015. © 2015 Wiley Periodicals, Inc.